The detection of mosaicism by prenatal BoBs™. (20th November 2012) - Cheng, Yvonne K.Y.; Wong, Cherry; Wong, Hoi Kin; Leung, Kwok On; Kwok, Yvonne K.; Suen, Andy; Wang, Chi Chui; Leung, Tak Yeung; Choy, Kwong Wai
ABSTRACT Objective The objective of the study was to evaluate the ability of a new prenatal diagnostic platform – prenatal BACs‐on‐Beads™ (BoBs™) in detecting mosaicism by comparison to quantitative fluorescence‐polymerase chain reaction (QF‐PCR). Methods A validation study of prenatal BoBs™ was firstly performed using 18 artificially constructing mosaic samples involving various aneuploidies and microdeletion conditions. Additionally, we compared the accuracy between prenatal BoBs™ and QF‐PCR for 18 archived clinical mosaic cases and nine chromosomally abnormal cell lines with reference to conventional karyotype results. Results In the validation study, BoBs™ allowed the detection of mosaicism at a level of 20–40%. Among the clinical mosaic cases, 14/18 cases were within the detection of BoBs™, 8/14 (57.1%) could be identified by BoBs™ and 6/9 (66.7%) by QF‐PCR, but 6/14 (42.9%) were missed by both tests. Three cases (16.7%) were detected by prenatal BoBs™ but missed by QF‐PCR, whereas QF‐PCR detected one case that was missed by BoBs™. The overall sensitivity of BoBs™ in detecting mosaicism is 44.4% (8/18), which is slightly higher than that of QF‐PCR (33.3%; 6/18). Conclusion Prenatal BoBs™ has a sensitivity of 57.1% in the detection clinical mosaic cases. According to the validation test, mosaicism of 20% or greater is detectable by the BoBs™ assay. © 2012 John Wiley & Sons, Ltd.